2020
DOI: 10.1038/s42004-020-00383-0
|View full text |Cite
|
Sign up to set email alerts
|

Internal water channel formation in CXCR4 is crucial for Gi-protein coupling upon activation by CXCL12

Abstract: Chemokine receptor CXCR4 is a major drug target for numerous diseases because of its involvement in the regulation of cell migration and the developmental process. In this study, atomic-level molecular dynamics simulations were used to determine the activation mechanism and internal water formation of CXCR4 in complex with chemokine CXCL12 and Gi-protein. The results indicated that CXCL12-bound CXCR4 underwent transmembrane 6 (TM6) outward movement and a decrease in tyrosine toggle switch by eliciting the brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…This and previous results [ 37 ] are consistent with our MD simulations. Similar findings were confirmed by mutagenesis experiments and MD simulations, suggesting that the mutations at L244 6.40 P and L246 6.42 P of the chemokine receptor CXCR4 do not affect its CXCL12 ligand-binding but noticeably reduce the calcium flux, leading to CXCR4 inactivation [ 25 , 45 , 46 ]. Very recently, Wang et al reported a cryo-EM structure of AVP-AVPR2-G s complex [ 20 ].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This and previous results [ 37 ] are consistent with our MD simulations. Similar findings were confirmed by mutagenesis experiments and MD simulations, suggesting that the mutations at L244 6.40 P and L246 6.42 P of the chemokine receptor CXCR4 do not affect its CXCL12 ligand-binding but noticeably reduce the calcium flux, leading to CXCR4 inactivation [ 25 , 45 , 46 ]. Very recently, Wang et al reported a cryo-EM structure of AVP-AVPR2-G s complex [ 20 ].…”
Section: Discussionsupporting
confidence: 53%
“…A previous study has shown that apo AVPR2-WT has constitutive activity and its mutant (AVPR2-D136A) has 2- to 3-fold higher constitutive activity in the absence of agonists [ 26 ]. In addition, the outward dynamic movement of the transmembrane helix 6 (TM6), which enlarges the cytoplasmic region of GPCR to facilitate G-protein coupling, is key to GPCR activation [ 25 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MM/PBSA binding energies of the TNKS inhibitors were calculated using the GROMACS program tool g_mmpbsa [ 19 ]. More detailed settings of the free energy calculations were described in our previous studies [ 20 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a result, in some cases, MD simulations, which calculate more detailed interaction energies, are required for providing complementary to molecular docking and more reliable results [ 25 ]. MD simulations can be used independently for investigations of conformational changes of specific molecules over a period of time [ 26 27 ]. These simulations can also be applied to optimize the structures of final complexes from molecular docking and provide insights of the ligand binding mechanism [ 23 25 28 ].…”
Section: Olecular D Ocking and M ...mentioning
confidence: 99%